2018
DOI: 10.1038/s41598-018-23542-9
|View full text |Cite
|
Sign up to set email alerts
|

A prominent air pollutant, Indeno[1,2,3-cd]pyrene, enhances allergic lung inflammation via aryl hydrocarbon receptor

Abstract: Chronic exposure to ambient polycyclic aromatic hydrocarbons (PAHs) is associated with asthma, but its regulatory mechanisms remain incompletely defined. We report herein that elevated levels of urinary 1-hydroxypyrene, a biomarker of PAH exposure, were found in asthmatic subjects (n = 39) as compared to those in healthy subjects (n = 43) living in an industrial city of Taiwan, where indeno[1,2,3-cd]pyrene (IP) was found to be a prominent PAH associated with ambient PM 2.5 . In a mouse model, intranasal exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 46 publications
0
27
0
Order By: Relevance
“…TGF‐β and IL‐10 take on potent anti‐inflammatory effects, repressing the expression of inflammatory cytokines of IL‐6 and TNF‐α . Wong et al reported that indeno [1,2,3‐cd] pyrene which was found to be a prominent PAHs associated with ambient PM2.5, and its treatment significantly altered the function of DC, including increased level of pro‐inflammatory IL‐6 and decreased generation of anti‐inflammatory IL‐10 . Another study indicated that a cigarette smoke‐induced COPD mice model exhibited an increased pro‐inflammatory immune response (increased expression of the TNF‐α and IL‐6) with a concomitantly decreased anti‐inflammatory immune response (Foxp3, IL‐10, and TGF‐β markers) compared with the control mice .…”
Section: Resultsmentioning
confidence: 99%
“…TGF‐β and IL‐10 take on potent anti‐inflammatory effects, repressing the expression of inflammatory cytokines of IL‐6 and TNF‐α . Wong et al reported that indeno [1,2,3‐cd] pyrene which was found to be a prominent PAHs associated with ambient PM2.5, and its treatment significantly altered the function of DC, including increased level of pro‐inflammatory IL‐6 and decreased generation of anti‐inflammatory IL‐10 . Another study indicated that a cigarette smoke‐induced COPD mice model exhibited an increased pro‐inflammatory immune response (increased expression of the TNF‐α and IL‐6) with a concomitantly decreased anti‐inflammatory immune response (Foxp3, IL‐10, and TGF‐β markers) compared with the control mice .…”
Section: Resultsmentioning
confidence: 99%
“…Asthma is characterized by chronic airway inflammation, and hyperresponsiveness (AHR) accompanied by mucus hypersecretion [1]. Triggers of allergic asthma include allergens, fungus (such as Aspergillus fumigatus [2]), viruses (mainly human rhinoviruses (HRV) [3]), and pollutants (including polycyclic aromatic hydrocarbons [4]) [5]. They interact with the airway epithelial cells to initiate the inflammatory response across the airways by releasing of cytokines, particularly IL-25, IL-33, and TSLP [5].…”
Section: Introductionmentioning
confidence: 99%
“…It is expressed universally in multiple cell types: mast cells, macrophages, dendritic cells, T cells, and epithelial cells. [5][6][7][8][9][10][11][12][13] Particulate matter of 2.5 mm or less in diameter (PM2.5) is very small and can enter the airways and reach the alveoli. These small PM sizes are partly eliminated by alveolar macrophages, but some of them (especially those of <1 mm in diameter [like ultrafine particles]) pass into the blood circulation.…”
mentioning
confidence: 99%
“…5,21 Also, PMassociated PAHs have been suggested to aggravate asthma in mice. 12 Nevertheless, how the intrinsic AhR in T cells responds to PM or PAHs and regulates allergic inflammation is not known.…”
mentioning
confidence: 99%